2014
DOI: 10.1016/j.jped.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of underdiagnosis and markers of high blood pressure risk in children aged 6 to 13 years

Abstract: Overweight and family history constitute the main risk markers of high BP in children. The low frequency of BP measurement in children observed in this municipality contributes to the underdiagnosis of the disease, with irreversible consequences for these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Although male patients have higher rates of pediatric hypertension, 2 female patients were more likely to undergo screening in our study, perhaps owing to contraceptive prescribing; measuring blood pressure is recommended before starting the oral contraceptive pill. 16 Previous studies found that obesity and family history were the most significant predictors of a high blood pressure reading in children 14,17 and that obese children were more likely to undergo screening. 14 However, we found no significant association between obesity or a record of a family history of hypertension and blood pressure screening.…”
Section: Discussionmentioning
confidence: 97%
“…Although male patients have higher rates of pediatric hypertension, 2 female patients were more likely to undergo screening in our study, perhaps owing to contraceptive prescribing; measuring blood pressure is recommended before starting the oral contraceptive pill. 16 Previous studies found that obesity and family history were the most significant predictors of a high blood pressure reading in children 14,17 and that obese children were more likely to undergo screening. 14 However, we found no significant association between obesity or a record of a family history of hypertension and blood pressure screening.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the studies selected their patients from the same schools where they studied, [15][16][17][18][19][20][21][22][23] with only four of them involving students coming from public schools, 15,19,20,22 whereas other four used data from patients who were already being followed up in an outpatient clinic. 8,[24][25][26] Two studies evaluated the same population of inpatients awaiting non-cardiac elective surgery 27,28 and one study obtained a sample from the general population.…”
Section: Characterization Of Studiesmentioning
confidence: 99%
“…The other measurement sites were: just below the thyroid cartilage, 23 the cricoid cartilage 8,30 and at halfway the height of the neck. 21,26 In only three studies the measurements had been taken as duplicates or triplicates, 15,23,25 a fact of little relevance due to the already well-documented reproducibility of this type of measurement. 13 Eleven (11) studies 8,16,17,19,20,22,23,[27][28][29]31 mentioned the training of examiners.…”
Section: Characterization Of Studiesmentioning
confidence: 99%
“…Apesar do aumento considerado da prevalência de HAS em crianças, a aferição da PA não é prática habitual nos atendimentos e acompanhamento pediátrico. Embora existam tabelas percentílicas de referência, programas eletrônicos para facilitar a classificação e equipamentos pediátricos adequados, o subdiagnóstico em crianças está documentado na literatura 11 . Aprofundar o conhecimento sobre a associação de medidas rotineiramente utilizadas pela prática clínica como antropometria e outras mais específicas, mas não mais complexa, como o NAF pode ser uma alternativa para triagem de PA elevada em crianças.…”
Section: Introductionunclassified
“…Nesse contexto, alguns estudos conduzidos com crianças brasileiras em idade escolar apontaram associação entre IMC [11][12][13] , perímetro de cintura 14 e PA elevada. Por outro lado, até o nosso conhecimento, não foram publicados pontos de corte de medidas antropométricas (IMC, perímetro de cintura e dobras cutâneas) e do NAF para predizer PA elevada em crianças brasileiras, por sexo, em idade escolar.…”
Section: Introductionunclassified